Ethno-STEM Mobile Apps in Formal Education: A Systematic Review of Design Principles, Cultural Adaptation, and Learning Outcomes - Indah Permatasari; Hasan S. Panigoro; Emli Rahmi (Universitas Negeri Gorontalo, 2026)
This study presents a systematic literature review examining the development and educational impact of ethno-STEM mobile applications used in formal education. The review aims to synthesize evidence regarding three main aspects: design principles and technical features of ethno-STEM mobile apps, the integration and cultural adaptation of local knowledge, and the learning outcomes reported for students. The review followed the PRISMA 2020 framework to ensure transparency and methodological rigor in the identification, screening, and synthesis of relevant studies. Literature was retrieved from the SCOPUS database using Boolean keywords covering publications from 2016 to 2026. After a structured screening process involving document type filtering and content-based eligibility criteria, five studies were included in the final qualitative synthesis. The findings reveal that most ethno-STEM mobile applications are developed using Android platforms and instructional design frameworks such as ADDIE, emphasizing multimedia integration, interactive visualization, and guided inquiry structures. Cultural knowledge is incorporated through approaches such as ethnopedagogy, ethnomathematics, ethnoscience, and dual representation of indigenous and scientific knowledge systems. However, cultural validation processes are commonly limited to expert reviews and user evaluations rather than participatory collaboration with community knowledge holders. The reviewed studies report positive educational outcomes, including improvements in mathematical problem solving, creative thinking, scientific literacy, and student engagement. Nevertheless, most evaluations rely on short-term interventions and limited methodological rigor, with little evidence of long-term learning impacts or identity development. Overall, the findings suggest that ethno-STEM mobile applications show strong pedagogical potential but require more robust cultural validation frameworks and longitudinal evaluation to support sustainable and culturally responsive STEM learning.